THE RELATIONSHIP BETWEEN WEIGHT GAINS DURING PREGNANCY WITH THE RISK OF PREECLAMPSIA - Noor Faridha; Heny Astutik; Kiswati Kiswati; Meisya Ika Rahmawati Debila Debila (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2022)
Pregnancy is a physiological process, however, a normal pregnancy can develop into pathology. WHO estimates that 15% of pregnant women develop complications. Preeclampsia is a pregnancy complication that can harm the mother and the baby. Gestational weight gain during pregnancy can result from overweight or pregnancy obesity, which is a risk factor of preeclampsia. The goal of this literature review is to determine the correlation between gestational weight gain and the risk of preeclampsia. This research methodology employed a Systematic Mapping Study, in which the article is selected based on the protocols and filters determined at the outset. The articles were investigated between 2016 and 2020 using the Google Scholar, PubMed, and DOAJ databases. The total population of 311 research articles and 7 sample articles describe the correlation between gestational weight gain and the risk of preeclampsia. 57% of 7 articles indicated that pregnant women had excessive weight gain, 71% of 7 articles indicated that women with preeclampsia have gestational weight gain and 43% of 7 articles indicated that there is a correlation between gestational weight gain and the risk of preeclampsia. Midwives are expected to improve the quality of antenatal care services to prevent preeclampsia by providing preeclampsia information and education, as well as screening for early detection.